2020
DOI: 10.3390/polym12091892
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imprinting of Bisphenol A on Silica Skeleton and Gold Pinhole Surfaces in 2D Colloidal Inverse Opal through Thermal Graft Copolymerization

Abstract: This study successfully fabricated BPA-imprinted poly(4-vinylpyridine-co-ethylene glycol dimethacrylate) (poly(4-VP-co-EGDMA)) quartz crystal microbalance (MIP-QCM) sensors on a silica skeleton surface and gold pinholes of silica inverse opal through surface-initiated atom transfer radical polymerization (SI-ATRP). The sensing features of the two MIP films on the structured silica surface and nano-scale local gold surface were investigated by measuring the resonant frequency change (∆f) in QCM sensors. The ∆f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…The higher values of the imprinting factor and of the binding capacity registered for BPA-MIP MPTES , compared to BPA-MIP DAMOT were in agreement with the conclusions drawn from the morpho-structural evaluation of films. According to other reported values for the imprinting factor, such as the one reported for nylon nanofibers (3.4 [32]) and the one reported by Yang and Park (2.15 [31]), the maximum F value of 3.03 found in this study is quite adequate.…”
Section: Reusability and Stability Of Filmssupporting
confidence: 70%
See 2 more Smart Citations
“…The higher values of the imprinting factor and of the binding capacity registered for BPA-MIP MPTES , compared to BPA-MIP DAMOT were in agreement with the conclusions drawn from the morpho-structural evaluation of films. According to other reported values for the imprinting factor, such as the one reported for nylon nanofibers (3.4 [32]) and the one reported by Yang and Park (2.15 [31]), the maximum F value of 3.03 found in this study is quite adequate.…”
Section: Reusability and Stability Of Filmssupporting
confidence: 70%
“…These results highlighted the impact of the film thickness and the discrete porous structure of BPA-MIP DAMOT film upon the rebinding performance. Chang et al [2] reported a maximum BPA adsorption of silica MIPs nanospheres of 444.6 µmol g −1 and Yang and Park [31] reported a Qmax of 170 mg g −1 . Hence, in this case, it seems like thinner films are more efficient for rebinding BPA and the maximum capacities are in good agreement with other reported values.…”
Section: Batch Rebinding Of Bpa On Bpa-mip and Nip Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffraction wavelength of the sensor red shifted evidently as the structure color changed. Moreover, the MIPC sensor detection for chlorotoxin (Wang et al, 2012), bisphenol A (Guo et al, 2012;Oh et al, 2020;Yang and Park, 2020), diethylstilbestrol (Sai et al, 2013), hormone, (Kalecki et al, 2020) and other molecules (Hong et al, 2020) have also been reported as shown in Table 1.…”
Section: Responsive Mechanisms Of Mipc Sensorsmentioning
confidence: 99%
“…Antibiotics Oxytetracycline (Wang et al, 2019a), clindamycin hydrochloride (Wang et al, 2019b), chloramphenicol (Sai et al, 2016(Sai et al, , 2019, sulfonamides (Zhang F. et al, 2018;Zhang Y. H. et al, 2018;Li et al, 2019;Lin et al, 2020) Organophosphates Parathion , methane phosphonic acid (Huang C. et al, 2018), monocrotophos (Hong et al, 2020) Explosives TNT (Lu et al, 2016(Lu et al, , 2017Fan et al, 2020), 2,6-DNT, 2,4-DNT (Dai et al, 2017b;Lu et al, 2017) and 4-MNT (Lu et al, 2017), RDX (Fan et al, 2020), HMX (Fan et al, 2020), CL-20 (Fan et al, 2020) Drug Dropropizine , drug delivery (Deng et al, 2018), sulpiride Proteins and amino acids Fibrinopeptide B (Resende et al, 2020), avidin (Jinn et al, 2019), S-layer proteins (Pan et al, 2019), glycoprotein , L-kynurenine (Rizvi et al, 2020), L-histidine (Chen et al, 2018), hormone (Dabrowski et al, 2019;Kalecki et al, 2020) Others Bisphenol A (Shin and Shin, 2019;Hong et al, 2020;Oh et al, 2020;Yang and Park, 2020;Zeng et al, 2020), 2,4-dichlorophenol (Qin et al, 2020), 2-butoxyethanol (Dai et al, 2017a), α-amanitin (Qiu et al, 2020), ethyl anthranilate (Zhang et al, 2019), benzocaine (Chen S. et al, 2019), testosterone (Kadhem et al, 2018), phthalate est...…”
Section: Category Analytesmentioning
confidence: 99%